Implementation of Brunner's Cognitive Learning Psychology Theory in Catholic Religious Learning - Sergius Lay (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
This research is motivated by the learning process of Catholic religious education in the classroom experienced as only for the sake of cognitive formation that is done simply. Cognitive formation is not an easy thing to do, but requires a strategy for the achievement of maximum learning outcomes. In reality, in the learning process, students follow more, so that their cognition is getting weaker. In this case, Jerome S. Brunner suggests that, cognitive theory becomes very important in achieving educational goals, including in Catholic religious education. Meanwhile, the purpose of this research is that students can achieve good mental or cognitive quality, not just intelligence alone. The method used in this research is the literature review method. The results of this study are first, cognitive learning theory is a theory in which it states that the learning process takes precedence over the learning outcomes. Second, the active participation of individuals in the cognitive process is the basis for achieving the learning objectives of Catholic religion. Third, Catholic religious teachers as facilitators who motivate and evaluate students in the learning process of Catholic religious education. Fourth, Catholic religious teachers can use Bruner's cognitive theory for the application of Catholic religious education learning in the classroom.